AKAD SYARIAH DALAM BISNIS - Nur’ain Harahap (LP2MTBM MAKARIOZ, 2018)
This study discusses Akad doing business according to Islamic sharia view. The Qur'an as the guidance ofMuslims lives has explicitly regulated business activities, and views business as a profitable and enjoyablejob, so the Qur'an strongly encourages and motivates Muslims to conduct business transactions in their lives.The Qur'an recognizes the deligative authority over property that is legally owned by an individual or a group.The Qur'an gives full independence to conduct any transaction, in accordance with the desired with the limitsset by Sharia. One of the conditions in implementing aqad activities, namely must be a sense of mutualpleasure between the beraqad. Where with the covenant someone is bound by the covenant either betweena person with God or between someone with his servants (other creatures). Allah justifies any contract inaccordance with his provisions, but besides Allah forbid any forms of contract that are inconsistent withIslamic shari'ah and the provisions of Allah. According to Islam a Muslim must commit to the agreement hedoes. Akad is the most important tool in the legitimate or not muamalah and become the ultimate goal ofmuamalah